The Double Movement Method from The Perspective of Fazlur Rahman (A Study of Misogynistic Hadiths and Their Implications) - Mamluatur Rahmah (Jurnal Studi Gender dan Anak, 2025)
Hadiths considered misogynistic have sparked various debates regarding the position of women in Islam. Literal interpretations without considering the social-historical context may reinforce gender injustice. This study aims to analyze these hadiths using Fazlur Rahman’s Double Movement theory to provide a more just and contextual understanding of the position of women in Islam. This research employs a library research method with a hermeneutic approach, examining primary sources such as hadith collections and academic literature published in the last ten years. Data was collected through critical analysis of relevant hadiths and analyzed with attention to historical, sociological, and anthropological aspects. The findings indicate that the statement about women being “deficient in intellect and religion” must be understood within the social context of 7th-century Arabia, not as a universal principle of women’s inferiority. Furthermore, hadiths regarding testimony, menstruation-related worship, and the prohibition of women traveling without a mahram reflect specific historical conditions that cannot be applied universally across all eras. The discussion emphasizes the importance of a hermeneutic approach to avoid patriarchal bias in understanding religious texts, encouraging a more reflective, just reading that aligns with the principles of Islamic justice. [Hadis-hadis yang dianggap bermuatan misoginis telah menimbulkan berbagai perdebatan terkait posisi perempuan dalam Islam. Penafsiran literal tanpa mempertimbangkan konteks sosial-historis berpotensi memperkuat ketidakadilan gender. Penelitian ini bertujuan untuk menganalisis hadis-hadis tersebut menggunakan teori Double Movement Fazlur Rahman guna menghasilkan pemahaman yang lebih adil dan kontekstual tentang posisi perempuan dalam Islam. Penelitian ini menggunakan metode studi kepustakaan dengan pendekatan hermeneutika, mengkaji sumber primer seperti kitab hadis serta literatur akademik terkini yang diterbitkan dalam sepuluh tahun terakhir. Data dikumpulkan melalui telaah kritis terhadap hadis-hadis terkait dan dianalisis dengan mempertimbangkan aspek historis, sosiologis, dan antropologis. Hasil penelitian menunjukkan bahwa ungkapan tentang perempuan sebagai “lemah akal dan agama” harus dipahami dalam konteks sosial Arab pada masa Nabi, bukan sebagai prinsip universal tentang inferioritas perempuan. Selain itu, hadis-hadis tentang kesaksian, ibadah saat haid, dan larangan bepergian tanpa mahram juga mencerminkan kondisi historis tertentu yang tidak dapat diterapkan secara mutlak di semua zaman. Diskusi menunjukkan pentingnya pendekatan hermeneutis dalam menghindari bias patriarkal dalam memahami teks keagamaan, sehingga mendorong pembacaan yang lebih reflektif, adil, dan sesuai dengan prinsip keadilan Islam].